(untitled) (Journal of Human Sciences, 2022)
The current study aims to identify the level of time management as a determinant of academic ambition among a sample of students of the Faculty of Arts at Sebha University. And the study relied on the descriptive analytical method. The sample’s society consisted of (190) male and female students that were chosen randomly. Consequently, after verifying the validity and reliability of the study tools, the study questions were answered. The results concluded that there is a statistically significant relationship between time management and the level of academic ambition among the study sample, there are no statistically significant differences at the level of ambition due to the gender variable, there are no statistically significant differences at the level of ambition due to the age variable, meaning that it is not statistically significant, while there are differences in the two dimensions (personal obstacles, the general dimension),There are no statistically significant differences in the two axes (planning, organization) attributable to the gender variable, i.e., it can be said that there are no statistically significant differences, while there are statistically significant differences in the two axes (time wasting and the general dimension), meaning that they are statistically significant, and there are no significant differences A statistic in the scale of time management attributed to the variable of age, and the study recommends the need to pay attention to the role of time and how to use it to create academic and scientific opportunities for university youth.